Predictors of health-related quality of life for children with neurodevelopmental conditions - Mahjoob, Maryam; Cardy, Robyn; Penner, Melanie; Anagnostou, Evdokia; Andrade, Brendan F.; Crosbie, Jennifer; Kelley, Elizabeth; Ayub, Muhammad; Ayub, Muhammad; Brian, Jessica; Iaboni, Alana; Schachar, Russell; et al. (Scientific reports, 2024)
Neurodevelopmental conditions can be associated with decreased health-related quality of life; however, the predictors of these outcomes remain largely unknown. We characterized the predictors of health-related quality of life (HRQoL) in a sample of neurodiverse children and youth. We used a cross-sectional subsample from the Province of Ontario Neurodevelopmental Disorders Network (POND) consisting of those children and young people in the POND dataset with complete study data (total n = 615; 31% female; age: 11.28 years ± 2.84 years). Using a structural equation model, we investigated the effects of demographics (age, sex, socioeconomic status), core features (Social Communication Questionnaire, Toronto Obsessive Compulsive Scale, Strengths and Weaknesses of attention deficit/hyperactivity disorder (ADHD)-symptoms and Normal Behavior), co-occurring symptoms (Child Behaviour Checklist), and adaptive functioning (Adaptive Behaviour Assessment System) on HRQoL (KINDL). A total of 615 participants had complete data for this study (autism = 135, ADHD = 273, subthreshold ADHD = 7, obsessive–compulsive disorder (OCD) = 38, sub-threshold OCD = 1, neurotypical = 161). Of these participants, 190 (31%) identified as female, and 425 (69%) identified as male. The mean age was 11.28 years ± 2.84 years. Health-related quality of life was negatively associated with co-occurring symptoms (B = − 0.6, SE = 0.20, CI (− 0.95, − 0.19), p = 0.004)) and age (B = − 0.1, SE = 0.04, CI (− 0.19, − 0.01), p = 0.037). Fewer co-occurring symptoms were associated with higher socioeconomic status (B = − 0.5, SE = − 0.05, CI (− 0.58, − 0.37), p < 0.001). This study used a cross-sectional design. Given that one’s experiences, needs, supports, and environment and thus HrQoL may change significantly over the lifespan and a longitudinal analysis of predictors is needed to capture these changes. Future studies with more diverse participant groups are needed. These results demonstrate the importance of behavioural and sociodemographic characteristics on health-related quality of life across neurodevelopmental conditions.